Evaluation of Downward Shortwave Radiation Products Over the Loess Plateau - Qianqian Tian; Shuhua Zhang; Weili Duan; Guanghui Ming (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2024)
Downward shortwave radiation (DSR) is a key component of the surface energy budget, influencing atmospheric circulation and climate change. DSR products derived from remote sensing observations or generated from reanalysis systems are commonly used as inputs for ecohydrological and climate models. The Loess Plateau is severely affected by soil erosion and has experienced frequent extreme weather events in recent years. Therefore, an accurate DSR product is crucial for accurately simulating climate change and surface-atmosphere processes on the Loess Plateau. In this study, newly released satellite DSR products CLouds, Albedo and Radiation Edition 3 data (CLARA-A3) and Moderate Resolution Imaging Spectroradiometer land surface Downward Shortwave Radiation Version 6.1 data (MCD18A1 V6.1), along with the reanalysis product Land component of the Fifth Generation European Centre for Medium-Range Weather Forecasts Reanalysis (ERA5-Land), were evaluated over the Loess Plateau and its surrounding areas. Intraday, daily, monthly, and seasonal DSR were evaluated against ground measurements which were collected from five observation networks. CLARA-A3 outperformed MCD18A1 and ERA5-Land on both monthly and daily scales. The root-mean-square error for monthly (daily) DSR from CLARA-A3, ERA5-Land, and MCD18A1 were 19.31 (31.3) W/m2, 25.36 (39.74) W/m2, and 25.03 (46.14) W/m2, respectively. The study explored potential factors contributing to significant errors in DSR products. Results indicated that snow cover was one possible factor influencing the error in MCD18A1, and CLARA-A3 exhibited greater sensitivity to terrain influence compared to ERA5-Land and MCD18A1. The findings can be the reference for selecting DSR products over the Loess Plateau.